The Effects of Sulfur on Skin Health of Apricot Workers - Senol, Mustafa; Ozcan, Atilla; Yologlu, Saim; Hazneci, Ersoy; Dogan, Gursoy (Annals of Medical Research, 2021)
None
Keywords: s /b: Apricot, sulfur, skin health.